Ileal mucosal bile acid absorption is increased in Cftr knockout mice - Stelzner, Matthias (BioMed Central, 2001)
BACKGROUND: Excessive loss of bile acids in stool has been reported in patients with cystic fibrosis. Some data suggest that a defect in mucosal bile acid transport may be the mechanism of bile acid malabsorption in these individuals. However, the molecular basis of this defect is unknown. This study examines the expression of the ileal bile acid transporter protein (IBAT) and rates of diffusional (sodium independent) and active (sodium dependent) uptake of the radiolabeled bile acid taurocholate in mice with targeted disruption of the cftr gene. METHODS: Wild-type, heterozygous cftr (+/-) and homozygous cftr (-/-) mice were studied. Five one-cm segments of terminal ileum were excised, everted and mounted onto thin stainless steel rods and incubated in buffer containing tracer (3)H-taurocholate. Simultaneously, adjacent segments of terminal ileum were taken and processed for immunohistochemistry and Western blots using an antibody against the IBAT protein. RESULTS: In all ileal segments, taurocholate uptake rates were fourfold higher in cftr (-/-) and two-fold higher in cftr (+/-) mice compared to wild-type mice. Passive uptake was not significantly higher in cftr (-/-) mice than in controls. IBAT protein was comparably increased. Immuno-staining revealed that the greatest increases occurred in the crypts of cftr (-/-) animals. CONCLUSIONS: In the ileum, IBAT protein densities and taurocholate uptake rates are elevated in cftr (-/-) mice > cftr (+/-) > wild-type mice. These findings indicate that bile acid malabsorption in cystic fibrosis is not caused by a decrease in IBAT activity at the brush border. Alternative mechanisms are proposed, such as impaired bile acid uptake caused by the thick mucus barrier in the distal small bowel, coupled with a direct negative regulatory role for cftr in IBAT function.